(untitled) - Taylor, Eric K. (Cambridge, 2000)
Using Folk Tales shows teachers how to take advantage of the unique literary characteristics of folk tales to facilitate language learning. It provides over forty ready-to-use activities and dozens of stories. Activities are suitable for all ages and range from beginning to advanced.
Keywords: English language; Study and teaching